6b-5b-7b+9b=

Simple and best practice solution for 6b-5b-7b+9b= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6b-5b-7b+9b= equation:


Simplifying
6b + -5b + -7b + 9b = 0

Combine like terms: 6b + -5b = 1b
1b + -7b + 9b = 0

Combine like terms: 1b + -7b = -6b
-6b + 9b = 0

Combine like terms: -6b + 9b = 3b
3b = 0

Solving
3b = 0

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Divide each side by '3'.
b = 0

Simplifying
b = 0

See similar equations:

| n^2-5n=-1 | | 11x+7=6x+7 | | 14x-126=4x-6 | | 38-6x=3x+23 | | 7-8x=25-15x | | 42-7x=11x+22 | | 2x+14=85-8x | | 2(x+2)=9+5x | | 12z^2+7z+5= | | 6q^2-24q+24= | | 2n^2=32 | | 11x^2-22x-2=0 | | 7x+5x=32 | | 12x-2y=-8 | | 5+20=x | | 2x+7(3x-7)=-20-6x | | 4x-2-5x-10=7x | | P^4-3p^2-18=0 | | 2x+4x+7=5x-13 | | 8x-3x+5=-x-4 | | (7x+3)-(2x+8)= | | (3x+8)(3x+3)= | | 4x+30=11x-33 | | 7(y-2)=4-2y | | 5zt+86z=40Fration | | 4x-2=x+11 | | 16x-43-39x=89 | | 4x+30=11x-23 | | 2x+6x-3=-1 | | x+24=2x | | 58d+3=-16d | | 9+3+x=43 |

Equations solver categories